Pengaruh Sektor-Sektor Ekonomi Prioritas dan Variabel Demografis Terhadap Konsumsi Energi Listrik di Provinsi Nusa Tenggara Barat - Qodariah, Lailan; Nurjihadi, Muhammad (Indonesian Journal Publisher, 2024)
Electrical energy has become the main pillar in modern human activities. Electrical energy consumption continues to increase from time to time, including in the Province of West Nusa Tenggara (NTB), whose economy is heavily supported by the tourism sector and the mining industry. Previous studies have proven that the increase in electrical energy consumption is triggered by various factors, both demographic and economic factors. This research aims to find out what factors determine the amount of electrical energy consumption in NTB Province. This quantitative research uses secondary data in the form of time series data from 2000-2022. The data in this study was analyzed using a multiple linear regression model. The results of this research conclude that the development of the tourism sector, industrial sector and population simultaneously have a significant influence on electrical energy consumption in West Nusa Tenggara Province. However, partially the development of the tourism sector and the development of the industrial sector have no effect on electrical energy consumption, while the population partially has a significant effect on electrical energy consumption in NTB Province.